(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
this article covers the life and scientific work of the great scientist and statesman, a bright representative of the Timurid dynasty, the great thinker Mirzo Ulugbek, whose name is inscribed in gilded letters on the pages of World Science. His outstanding contribution to the development of astronomy, mathematics, geometry, geography and a number of other sciences, the accuracy of the calculations he carried out in the Middle Ages, has still left the people of modern science lol.